L’Église verte ? La construction d’une écologie catholique : étapes et tensions - Étienne Grésillon; Bertrand Sajaloli (VertigO)
The article shows the spiritual foundations of the Catholic understanding of the nature and construction phases of a Christian ecology. The work analyses the positions taken by the Christians of the environment that are sometimes discordant. Following an accusation by some environmentalists and intellectuals to be responsible for environmental crises the Catholic Church was first conducted a philosophical and spiritual response by showing that man is responsible for world history (anthropocentric) and the life on earth is attached to god (theocentrism). To overcome this opposition, the Vatican does not speak of the ecological disaster and has defined a "human ecology" Catholic defending the traditional values of the church (prohibition of contraception and medically assisted reproduction technologies...). It shifts the debate on moral issues and it divides the believer. Finally, another vision emerges from the church criticizing consumerism and critical commercial vision of nature. Today, these fields of ecology Catholic co-exist and there is much debate, especially in France. But these conflicting ideas (anthropocentrism and theocentrism) determine therefore the first fragile political ecology of Catholics for ecology.